Identity of Baker’s species described in the Oriental leafhopper genus Pythamus (Hemiptera: Cicadellidae) with description of a new genus - Wei, Cong; Webb, Michael D.; Zhang, Yalin (Zootaxa, 2014)
Baker’s (1915) species described in the Oriental leafhopper genus Pythamus Melichar are revised. One species, Pythamus melichari Baker 1915, is placed in a new genus, Pythochandra Wei & Webb, gen. n.. The four varieties of P. melichari described by Baker (1915, 1923) (borneensis, bilobatus, decoratus and singaporensis) are elevated to species level and placed in the new genus stat. n., comb. n.. All species are briefly described and a key is provided for their separation. Two other species, Pythamus productus Baker and P. decoratus Baker, known only from females, are retained in Pythamus pending further studies.